PENILAIAN RESIKO TEKNOIOGI INFORMASI & KEAMANAN SISTEM INFORMASI DENGAN MENGGUNAKAN FRAMEWORK COBIT 4.1 DAN GUIDELINES NIST SP 800-30 ( Studi Kasus : Rumah Sakit Umum Dr Slamet Garut ) - Yana aditia gerhana; Erdiansyah Erdiansyah Erdiansyah; Undang Syarifudin (JURNAL ISTEK, 2011)
Every organization have a goal. In the digital era, organization use automated information technology to process their information for better support for their goals, and risk management plays and important role to protect information assets of organization and for that purpose can be accomplished. An effective risk management process is an important component of the success of information technology security program. The principle objectives of an organization’s risk management should be protect organization and the ability to perform their purpose is not to protect information technology assets only. For this risk management process should not be treated purely as a function but the technique is the basis of the management functions of the organization.